KAJIAN PSIKOLOGIS TERHADAP REALITAS PERKEMBANGAN PESERTA DIDIK - Ramadlani, Afra Shafa; Robandi, Babang (IKIP Siliwangi, 2025)
This article discusses about the psychological development of students, where psychological development is integrated with activities experienced in daily life, life, and the environment with the natural surroundings continuously and is an inseparable unit. Psychological development is a change that occurs in the individual as a result of the learning process and is adjusted to the conditions of students' psychological development. (Mulyana, 2019) This research was conducted using the library research method, namely by finding and digging up information or data through references or libraries from books or scientific journals. The results of the literature study, it was found that in accordance with the principle of development that physical development is a part related to the cognitive, emotional, social, and moral domains because psychological development will affect children to adjust their development abilities. By paying attention to the psychological aspects of students, this can provide opportunities for students to be able to learn according to their interests, talents, tempo and effective learning methods for them.Keywords: Psychological, Students